Tindakan Pengurangan Risiko Penularan HIV Pada Pengguna Narkoba Suntik (Penasun) - Andi Mulawarman; Bagoes Widjanarko; Zahroh Shaluhiyah (Jurnal Promosi Kesehatan Indonesia, 2011)
The risk reduction action among IDU’s is needed to reduce the emerging of new case of HIV transmission through their risk behavior either in drug using practices and sexual practices. This study was aimed to analyze determinant factors to risk reduction action of HIV transmission among IDU’s in Makassar City. It was an explanatory study, employs a cross sectional research design and combining between Health Belief Model and Social Learning Theory. Target population in this research was all IDU’s in Makassar City that have been reached by three NGOs and involving in individual risk assessment. There were 97 respondents involved in this research, selected by applying systematic random sampling technique. Questionnaire was used for collect data and analyze with chi square to measure bivariate correlation. Logistic regression was employed for multivariate analysis. Out of the 97 IDU’s, 60,8% IDU’s experienced consistency in risk reduction action adherence. Logistic regression analysis showed that risk reduction action dominantly influence by knowledge of HIV/AIDS.